KETANGGUHAN PANCASILA SEBAGAI IDEOLOGI BANGSA INDONESIA DI ERA REVOLUSI INDUSTRI 4.0 - Rahma, Hanum Lauditta; Habibah, Siti Maizul (Universitas Tidar, 2024)
The era of disruption that occurred globally had affected all human life in various fields, both in the economic, social, cultural, political, educational and other fields. Pancasila as the basis of the state and as the nation's view of life, must not be abandoned in order to achieve the values of the precepts contained in Pancasila. Pancasila holds an important role to be a filter of new values by applying the values of Pancasila in all aspects of life. The research method used in this article is qualitative research and library research method. The industry 4.0 with all the disruptions that follow needs to be addressed critically by living the values as one of the foundations that are maintained in the disruption of the industry 4.0.